Pengaruh Valuasi Ekonomi SDA terhadap Kebijakan Lingkungan Berkelanjutan: Penelitian - Bonaraja Purba; Gebatania Pakpahan; Sarah Desnita Manihuruk; Lidya Vanya F. Sihombing; Agustin Olivia Simamora (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of natural resource economic valuation on sustainable environmental policies in Indonesia. The economic valuation of natural resources is a scientific approach that assigns monetary value to the benefits and functions of the environment, whether they have a market price or not. Using a qualitative descriptive method, this research explains how economic valuation supports efficient and environmentally equitable policy-making. The findings indicate that the implementation of valuation methods—both demand-based and non-demand-based approaches—helps policymakers identify policy alternatives that balance economic growth with environmental preservation. However, limitations in data availability, human resource capacity, and understanding of valuation concepts remain major challenges. Strengthening environmental data systems, providing expert training, and enforcing valuation-based regulations are essential steps to ensure optimal application. Therefore, economic valuation serves not only as a financial assessment tool but also as a strategic foundation for achieving fair, efficient, and sustainable environmental policies.